ANALYSIS OF INSTAGRAM USAGE AS A MEDIA FOR PUBLICATION AND PROMOTION OF THE 2023 ARTJOG FESTIVAL: ANALISIS PENGGUNAAN INSTAGRAM SEBAGAI MEDIA PUBLIKASI DAN PROMOSI FESTIVAL ARTJOG 2023 - Nurcahyati, Desy; Salman Mohammadi Saragih, Dzikrullah (Arty: Jurnal Seni Rupa, 2024)
The existence of fine arts in Indonesia such as the ARTJOG festival has grown a lot with many new expressions poured into unique creativity by many local and world artists. To maintain the existence and development of fine art requires several strategies, one of which is to adapt to the times and utilize social media as a means of disseminating fine art to the general public. This research aims to analyze the influence of one of the popular and widely used social media in the world, namely Instagram, on the progress of the artjog festival in 2023. The research uses a descriptive qualitative method by presenting data obtained based on the results of observation and documentation collection contained in ARTJOG-themed content contained on the official Instagram @artjog.id and other Instagram accounts during the specified period. The results obtained are that Instagram has an influence as a publication and promotion medium for the ARTJOG 2023 festival which displays content that is useful as material for insight, inspiration, and entertainment to the audience of Instagram users.